Relationship Factors Social Farmers on The Level Implementation Technology IPM of Rice Plants - Muzizah Zizah; Ambar Susanti (AGARICUS: Advances Agriculture Science & Farming, 2021)
Sendangrejo Hamlet is one of the areas of Banjardowo Village , Jombang District which is the main rice producer. Based on data obtained from the Farmers Group Association (GAPOKTAN) in the hamlet, farmers still carry out conventional and scheduled pest and disease control, it is necessary to implement Integrated Pest Management (IPM) to get better quality and quantity of production. This study aims to determine the relationship of farmer social factors to the implementation of integrated pest and disease management technology (IPM) on rice plants in Sendangrejo Hamlet, Banjardowo Village, Jombang District. The research was carried out. The method in this study used descriptive analysis method, with a variable consisting of 2 variables, namely variable X including age, education, and length of farming while for variable Y consisted of IPM implementation. Respondents were taken by 20 respondents from 154 farmer populations. Questionnaire data (questionnaire) was used with an ordinal scale. It is known that there is a significant relationship between social factors including age, education and duration of farming on the level of IPM implementation on rice plants in Sendangrejo Hamlet, Jombang District. Keywords: Social Factors, IPM Implementation, Rice Plants.